Newborn screening for Duchenne muscular dystrophy: the perspectives of stakeholdersResearch in context - Charli Ji; Didu S. Kariyawasam; Hugo Sampaio; Michelle Lorentzos; Kristi J. Jones; Michelle A. Farrar (The Lancet Regional Health. Western Pacific, 2024)
Summary: Background: The rapidly evolving clinical landscape of Duchenne muscular dystrophy (DMD) is driving innovative approaches for early diagnosis through genomic newborn bloodspot screening (NBS). However, the potential impact of these programs on families and healthcare systems remains unexplored. This study assessed the perceived benefits, harms, barriers, and enablers for DMD NBS amongst primary caregivers of children with DMD and healthcare professionals (HCPs). Methods: This Australian multi-centre cross-sectional study used a mixed-methods convergent methodology. Participants completed a codeveloped questionnaire and their perceptions on the utility, model of care, and processes of DMD NBS were thematically analysed. Findings: Participants included 50 caregivers and 26 HCPs (68.5% and 53.1% response rate respectively). Most caregivers (40/50, 80%) perceived net benefits of DMD NBS and highlighted an early diagnosis as actionable knowledge, even with the current paucity of disease modifying therapies. This knowledge was valued to enable access to multidisciplinary supportive care (29/50, 58%), clinical trials (27/50, 54%), psychological support (28/50, 56%), inform reproductive planning (27/50, 54%), and facilitate financial planning based on the future needs of their child (27/50, 54%). Whilst HCPs acknowledged these opportunities, only 16/26 (61.5%) believed there were definite net benefits, with notable concerns over the psychological harms of diagnostic knowledge without a recourse to disease modifying therapeutic intervention early in life. Interpretation: Caregivers and HCPs perceived a range of potential benefits of DMD NBS. Health system readiness will be founded on developing an integrated model of care that not only supports the psychosocial and information needs of families receiving a newborn diagnosis of DMD, but also provides care and clinical surveillance for individuals for whom a diagnosis may remain uncertain. Funding: Medical Research Futures fund (GNT2017165, MRF2015965).